Menstrual Hygiene Awareness ,Practices Adopted By Adolescent Girls And the Factors Associated With School Absenteeism - Harshdeep Joshi; Syed Shuja Qadri; Bhagwant Payghan; Swapna Kadam (Global Journal of Medicine and Public Health, 2024)
Background Safe practices during menstruation can not only be instrumental in promoting reproductive health but also help in utilizing education to its full potential by reducing drop outs from school.